2018
DOI: 10.1016/j.clinbiomech.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of real-time biofeedback on peak knee adduction moment in patients with medial knee osteoarthritis: Is direct feedback effective?

Abstract: Real-time biofeedback directly on the knee adduction moment is a promising option for encouraging gait modifications to reduce knee loading, however only when combined with specific instructions on how to modify the gait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 34 publications
(55 reference statements)
1
77
0
1
Order By: Relevance
“…representing true MCF and LCFs. This is of great importance considering so many studies stray beyond simple linear scaling (Fregly 2007;Shull et al 2013a;Ogaya et al 2014;Miller et al 2015;van Den Noort et al 2015;Liu et al 2016;Richards et al 2017). Two of the main limitations of this study were the small sample size and not randomizing the order of gait alterations, although beyond the scope of this study, this restricted detection of meaningful clinical results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…representing true MCF and LCFs. This is of great importance considering so many studies stray beyond simple linear scaling (Fregly 2007;Shull et al 2013a;Ogaya et al 2014;Miller et al 2015;van Den Noort et al 2015;Liu et al 2016;Richards et al 2017). Two of the main limitations of this study were the small sample size and not randomizing the order of gait alterations, although beyond the scope of this study, this restricted detection of meaningful clinical results.…”
Section: Discussionmentioning
confidence: 96%
“…Directing researchers to tailor treatments to the individual patient (Gerbrands et al 2014;Shull et al 2015;Favre et al 2016). One such study has shown that more patient-specifically assigned toe-in and toe-out walking can better reduce the peak KAM, a controversial surrogate for the medial contact force (Creaby 2015;Manal et al 2015;Richards et al 2018), when compared to uniformly assigned modifications (Uhlrich et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This study uses data collected for a previous study 27 with forty participants with medial KOA. Data from 35 of 40 participants were analyzed; demographics are presented in Table I.…”
Section: Participantsmentioning
confidence: 99%
“…Ethical approval was granted by the VUmc Medical Ethics committee and all participants provided written consent. Inclusion and exclusion criteria for the study are described in Richards et al 27 .…”
Section: Participantsmentioning
confidence: 99%
“…Recent research suggests remote observations may differ than those made in the lab or clinic [10][11][12], and thus may provide additional information for informing clinical decision making. Additionally, remote observation could be used as an endpoint for assessing efficacy of interventions designed to target specific biomechanical indices (e.g., using biofeedback to reduce knee loading [13]). Taken together, these developments suggest that remote observation of patient biomechanics during daily life is emerging as an important tool for improving human health.…”
Section: Introductionmentioning
confidence: 99%